Analisis Pengaruh Prestasi Akademik, Pengalaman Magang, Kompetensi dan Motivasi Kerja terhadap Kesiapan Kerja Mahasiswa/I Universitas Gunadarma Jurusan Manajamen Region Depok - Alfira Azka Fidiyanti; Mohammad Abdul Mukhyi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of academic achievement, internship experience, competence, and work motivation on the work readiness of Gunadarma University Management students in the Depok region. The research employed a quantitative method using primary data collected through questionnaires. A total of 250 valid responses were obtained using a non-probability sampling technique with purposive sampling. Data analysis was conducted using Smart PLS 4 software with several testing stages, including convergent validity, Average Variance Extracted (AVE), composite reliability, Cronbach’s alpha, discriminant validity, R-square test, predictive relevance (Q²), and hypothesis testing. The results indicate that academic achievement, internship experience, competence, and work motivation significantly influence students’ work readiness, both directly and indirectly. These findings highlight the importance of enhancing practical experience and internal motivation among students to better prepare them for the increasingly competitive job market.